How does emotional insecurity affect non-suicidal self-injury among Chinese early adolescents: a longitudinal study - Xingcan Ni; Qiao Liang; Xiaoyan Liao; Huahua Wang; Chengfu Yu (BMC, 2024)
Abstract Background Non-suicidal self-injury (NSSI) is a serious public health concern. Emotional insecurity is a crucial predictor of NSSI among adolescents. However, few studies have elucidated the specific mechanisms between emotional insecurity and NSSI. Methods This study employed a longitudinal research design, using a sample of 886 Chinese early adolescents (M age at T1 = 10.62 years, SD = 0.77 years; 47.40% females), and conducted two surveys six months apart to examine the mediating role of peer exclusion between emotional insecurity and NSSI, as well as the moderating effect of school climate. Results The results indicated that peer exclusion significantly mediated the connection between emotional insecurity and adolescent NSSI. Moreover, school climate significantly moderated the connection between emotional insecurity and peer exclusion. Specifically, the impact of emotional insecurity on peer exclusion was significant only in adolescents who reported a negative school climate, but non-significant in those who reported a positive school climate. Conclusions These findings provide a robust theoretical foundation and practical insights to help inform the prevention of and interventions for NSSI in adolescents.